HEGEMONI DAN DOMINASI PERUSAHAAN SEMEN TERHADAP PENDUDUK DI WILAYAH PEMBANGUNAN PABRIK SEMEN DALAM SAMIN VS SEMEN - Fredy Nugroho Setiawan (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2016)
Samin vs Semen is a documentary film portraying efforts of cement companies supported by the government to build cement plants near the Samin followers lands against resistance from Samin followers and nearby villagers who believe the activities of cement factories will harm their farmlands. Regarding Gramscian premises on hegemony and domination, this study describes some actions undertaken by the cement companies to cope with the resistance. The results of the study show that the cement companies, assisted by the government through its apparatus of state coercive power, attempt to dominate and hegemonize the local villagers. The domination of cement companies can be seen through a series of coercive measures of government apparatuses in handling the resistance.The hegemony, on the other hand, is yet to be proven due to the limitation of data from the film, which only takes the viewpoint of Samin followers and their proponents. Nevertheless, indications leading to hegemony exist although consent of the people remains subtle.